Ubiquitous Computing at its best: Serious exercise games for older adults in ambient assisted living environments – a technology acceptance perspective - Philipp Brauner; Andreas Holzinger; Martina Ziefle (EAI Endorsed Transactions on Serious Games, 2015)
Ubiquitous computing and ambient assisted living environments offer promising solutions to meet the demographic change. An example are serious games for health care: Regular exercises mediated through games increase health, well-being, and autonomy of the residents whilst at the same time reducing the costs for caregiving. To understand which factors contribute to an increased acceptance of such exercise games in ambient assisted living environments, a prototypic game was evaluated with 32 younger and 32 older players. Game performance is influenced by age, need for achievement, and also gender. Acceptance and projected use are related to the believe in making the game a habit, current gaming frequency, and social influences. Notably, the game increased the perceived health of the subjects, which is an important issue. This article concludes with guidelines to successfully introduce serious exercise games into health care and future ideas to realize social inclusion in game design.